Discourses of poverty in literature : assessing representations of indigence in post-colonial texts from Botswana, Namibia and Zimbabwe - Butale, Phenyo (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015